Unbalanced intake of methyl donor supplements, may lead to DNA methylation and cause breast cancer in offspring - Arefhosseini Seyed Rafie; Alijani Sepideh; Mohammadi Sumaieh (Forensic Science Today - Peertechz Publications, 2020)
Statistical data in Iran reflects a worrying trend for an increased incidence of breast cancer. recent national data on average annual crude incidence for primary breast cancer indicated 22.6 (95%CI 22.1-23.1) per 100,000. It seems that genome encoding with no changes in the sequence of DNA contributes to Lamarck's theory as a probable causative factor for the deterioration of this disorder by supplementation. Unconscious methylation of DNA by environmental factors make genetic modifications through epigenetic process in nucleotides that create new make up for DNA and DNMTs, expedite one of the most prevalent health disorders. Uterus environment, youth up to a retired and postmenopausal age are periods for changes in genome assembly that include tiny alterations in CpG islands. A review article had been performed by the electronic search for the manuscripts that had been published among current databases and declared facts about the produced results and the main proves had ascertained from the present articles. They were included by the Med Line and PubMed database and Iran's vital statistics. As a result consumption of selected nutrients has the ability for methylation by group donors and causes an actual transfer of a methyl to the C5 carbon of cytosine for making 5-methylcytosine. Characteristic of a living organism referred to the Genetic and Epigenetic information and unbalanced intake of selected nutrients with dual function like folic acid persuades the creation of a genetic foundation for breast cancer in offspring.